2015
DOI: 10.17557/.23190
|View full text |Cite
|
Sign up to set email alerts
|

YIELD AND QUALITY OF BLACK CUMIN (Nigella sativa L.) POPULATIONS: THE EFFECT OF ECOLOGICAL CONDITIONS

Abstract: The experiment was carried out in two vegetation seasons of 2013 and 2014 at the Isparta and Eskisehir ecological conditions. The main purpose of the study was to determine the effects of years and locations on seed yield, some yield-related traits, essential oil content and fixed oil ratio of black cumin populations. In the study, black cumin populations were obtained from Burdur, Tokat, Usak, Eskisehir and Antalya provinces. The experiments were arranged according to a randomized complete-block design with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 8 publications
3
18
1
2
Order By: Relevance
“…Sufficient moisture in the soil promotes the nutrition uptake of the plants, so rainfall in the first year increased the seed yield. Similar results that were obtained in other studies have also reported that seed yield and other plant caharecteristics varied depending on the climatic conditions of the year (Sadeghi 2009;Ghamarnia & Jalili, 2013;Kara et al 2015).…”
Section: Seed Yield and Its Componentssupporting
confidence: 89%
See 2 more Smart Citations
“…Sufficient moisture in the soil promotes the nutrition uptake of the plants, so rainfall in the first year increased the seed yield. Similar results that were obtained in other studies have also reported that seed yield and other plant caharecteristics varied depending on the climatic conditions of the year (Sadeghi 2009;Ghamarnia & Jalili, 2013;Kara et al 2015).…”
Section: Seed Yield and Its Componentssupporting
confidence: 89%
“…In comparison to previous studies, the essential oil content of the present results were lower than the values reported: 0.5% (Bourgou et al 2010), 0.5-1.6% (Ramadan 2007), 0.27-0.35% (Toncer & Kızıl, 2004, while showing parallels with the findings of Benkaci et al (2013) and Kara et al (2015). Kara et al (2015), Mohammadi et al (2016) and Mazaheri et al (2019) reported that fixed oil content varied between 26.0-32.5%, 31.6-40.0% and 34.0-39.0%, respectively. These differences might have been due to air temperature, precipitation, soil fertility, agronomic conditions and harvest stages (Telci 1995; Kulan et al 2012; Kara et al 2015)…”
Section: Essential Oil and Fixed Oil Contentsupporting
confidence: 69%
See 1 more Smart Citation
“…As with other cultivated plants, the yield and quality of the product to be obtained in medicinal aromatic plants results from the interaction of the genetic makeup of the plant material with the ecological conditions of the region and agronomic applications [13,14,15,16,17,18]. For this reason, it is of great importance to determine the most appropriate agronomic applications by the researches that will be carried out in order to produce high yield and quality products in a region.…”
Section: Resultsmentioning
confidence: 99%
“…Takođe, istraživanja tehnologije gajenja nisu vršena ni u Republici Srbiji, pa se raspolaže samo sa rezultatima istraživanja realizovanim u državama Bliskog istoka, Severne Afrike, Indije, Pakistana i saudijskog poluostrva. Razlike u produktivnosti i kvalitetu crnog kima, zavisno od agroekoloških uslova u radovima spominje više istraživača iz ovih oblasti [11,12,13,14]. Dokazano je da najbolji hemijski sastav i terapeutsko dejstvo ima seme i ulje, proizvedeno u aridnim i semiaridnim područjima [15,16,17,18].…”
Section: Uvodunclassified